The Relationship between Mothers’ Education Level, Knowledge Level, and Family Support, as well as the Role of Health Cadres, with the Motivation Level of Mothers of Toddlers to Visit the Posyandu in Takerharjo Village - Tri Yeni Fahmawati; Dwiyanti Puspitasari; Wahyul Anis (Rifa'Institute, 2026)
Introduction: The posyandu plays a strategic role in improving maternal and child health, and its success depends on the active participation of mothers of toddlers in routine visits. However, posyandu visit rates in Takerharjo Village remain suboptimal and fluctuate over time, influenced by factors such as mothers’ education level, knowledge about posyandu, family support, and the role of health cadres. Objective: To analyze the relationship between mothers’ education level, knowledge level, and family support, as well as the role of health cadres, with the motivation level of mothers of toddlers to visit the posyandu in Takerharjo Village. Method: This study employed a quantitative approach with a cross-sectional design. The research sample consisted of 81 respondents who met the inclusion criteria, selected using a cluster random sampling technique. The research instruments were questionnaires measuring education level, knowledge level, family support, the role of health cadres, and the motivation level of mothers of toddlers to visit the posyandu. The data were analyzed using the Chi-square test. Result and Discussion: Mothers’ knowledge level and family support showed a significant relationship with the motivation level of mothers of toddlers to visit the posyandu in Takerharjo Village. Mothers with good knowledge levels and high family support tended to have higher motivation to attend posyandu visits. Meanwhile, mothers’ education level and the role of health cadres did not show a significant relationship with the motivation level of mothers of toddlers to visit the posyandu. Conclusions: Most mothers had a high level of education, knowledge, family support, and motivation to visit the posyandu. Although the role of health cadres was generally rated as good, only mothers’ knowledge level and family support showed a significant relationship with motivation to visit the posyandu, while education level and the role of health cadres did not.